A Further enhancement of Boyer-Moore Horspool algorithm for dictionary to be applied in MS Word 2007 - Cunanan. Sarah Jane S. and Sapnay, Mary Joyce H. 4 0 16; 5 (2010)
u
Undergraduate Thesis (BS in Computer Science) - Pamantasan ng Lungsod ng Maynila, c2010.
Keywords: 2 -- 0; 6; 20; 20; 2